Análise de falhas, monitoramento e controle da corrosão em processo industrial de produção de biodiesel - Carlos Eduardo de Almeida Souza Torres (2017)
The use of biomass derived fuels has been identified as a technical alternative capable of minimizing the world's dependence on fossil fuels as well as the environmental damage caused by its burning. In line with a worldwide movement of the Oil & Gas companies in the search for alternative sources of energy, in 2008 PETROBRAS created the integral subsidiary PETROBRAS BIOCOMBUSTÍVEL - PBIO, today among the largest biodiesel producers in Brazil. The processing technology deployed in the company's units is based on the reaction of transesterification via the methyl route with basic homogeneous catalysis. In this process, the neutralization of the biodiesel and glycerine streams is carried out with the in-line dosage of hydrochloric acid solution. Considering that corrosion is an important degradation mechanism in the company's biodiesel plants, in order to develop and implement adequate means for its prevention, this work includes field evaluations, in-service and laboratory tests, involving techniques electrochemical and analytical methods to evaluate the corrosion mechanisms in the process. Different materials were evaluated at different levels of deepening. AISI 316L and AISI 904L stainless steels were tested in the welded condition, with individual analysis of the major regions of the joint. The results suggest that AISI 904L steel is more suited technically and economically than AISI 316L for the most critical points in the process. It was verified that under certain conditions the performance of the AISI 317L steel is similar to the performance of the AISI 904L. The electrochemical tests demonstrated that the corrosion resistance of AISI 316L and AISI 904L stainless steels can be significantly deteriorated by welding procedures, even without the occurrence of sensitization, possibly due to the influence of galvanic cells in the region of the weld. The correlation of CFD analysis with corrosion morphology in a failed part in service in the industrial biodiesel production process indicates that continuous in-line mixing of two low miscibility fluids developed in multiphase flow and with high conductivity gradients and chloride content between phases, it is prone to the occurrence of severe localized corrosive attack. The practical results generated by this research confirm the high capacity that the monitoring and control of corrosion has to add value to the industrial units of production.